Managing the socioeconomic and cultural factors of primary school dropout and effects on industry productivity levels in District Kech, Balochistan (KASBIT Business Journal, 2021)
School dropout is known to be a major issue individually, socially, educationally, and economically. Primary school dropout has been increasing in Pakistan in general and in Balochistan in particular. The determinants of primary school dropout vary across the province to province and district to district. This study finds the determinant of primary school dropout in district Kech of Balochistan. Primary data has been collected randomly from all tehsils of the district. Data were collected from 100 respondents using the Z-score method of sample size selection. Moreover, the study uses frequency distribution and charts to represent the data and applies Cronbach’s Alpha for the reliability of the responses. The findings of the study showed that there are many economic, social, and cultural factors that are causing primary school dropout in the district such as distance of the school from home, uneducated parents, cultural issues regarding female education, lack of transportation, child labor issue, non-availability of teachers, a high number of dependent children and unemployed parents. Thus, it is recommended that the Government should take into consideration the aforementioned factors to improve human capital and business productivity across the industries.
Keywords: Primary school dropout; Socioeconomic factors; cultural factor